Syntrophic growth of auxotrophic strains of Neurospora crassa by cross-feeding - A. Pandit; P. Delhi; R. Maheshwari (Fungal Genetics Reports, 1997)
Vigorous growth occurred when conidia of two heterokaryon-incompatible auxotrophic strains of N. crassa were mixed on minimal medium. The syntrophic growth could often, but not always, be propagated through several subcultures using minute conidial inocula. We demonstrate that growth of auxotrophic strains occurred without hyphal fusion by cross-feeding.